STUDENT’S READING SKILL PROBLEM IN PERGURUANTAMAN MADYA (SMA) TAMAN SISWA PEMATANG SIANTAR - RENINDA TAMBUNAN; RIANTI TESALONIKA SIMANJUNTAK; FITRI SIMAMORA; YOLANDA SIMANJUNTAK; SELVIANA NAPITUPULU (CV KULTURA DIGITAL MEDIA, 2022)
This research was conducted with the aim of knowing the problems of students' reading skills. The method in this research is the classroom action research method. The subjects or participants in this study were at SMA TAMAN MADYA TAMAN SISWA PEMATANGSIANTAR, to be precise, the class XII students with the number of participants were 22 students. Of the five aspects of reading comprehension, vocabulary experienced the highest increase, while the lowest increase was in the main idea. The purpose of the Think Aloud Method is for students to better understand the text, find the main idea, detailed information, inference, reference and vocabulary understanding, all of which increase. The Think Aloud method not only makes reading learning more interesting, but also improves students' ability to understand texts